The Effect of Essential Fatty Acids for the Somatic Growth in Nauplii of Calanus finmarchicus - Leiknes, Øystein; Etter, Siv A.; Tokle, Nils E.; Bergvik, Maria; Vadstein, Olav; Olsen, Yngvar (Frontiers in Marine Science, 2016)
The growth of Calanus finmarchicus nauplii was studied through three spawning seasons (2007, 2009 and 2011) using flow-through tubes. Natural seston was collected every second day and added as food source using a peristaltic pump. A mixture of cultured microalgae supplied in surplus concentration was used as a control treatment. No significant correlation between growth and food concentration measured as Chlorophyll a (Chla) or particulate organic carbon (POC) was detected, but the growth rate was significantly related to the content of EPA (20:5n-3) and DHA (22:6n-3) in the seston. The growth rate was overall higher for nauplii fed cultured microalgae compared to the nauplii fed natural seston. Although the nauplii fed algae cultures were fed surplus food, the growth did vary between the growth periods. Furthermore, the growth rate for nauplii fed natural seston and for nauplii fed cultured algae were positively related, suggesting that the maternal condition and the food quality experienced by the mothers could explain some of the variation in naupliar growth rate. We present lipid class data on Calanus finmarchicus eggs from field samples that, contrary to previous studies, showed a high content of wax esters. Fatty acid analyzes of eggs, nauplii stages and copepodites from field samples showed that eggs and nauplii have a similar fatty acid composition and that the main increase in the content and share of DHA and EPA was from nauplii to copepodite. The secondary production measured as naupliar growth was compared to the secondary production measured as carbon specific female egg production rate. The secondary production measured as egg production was generally higher than the secondary production measured as naupliar growth early in the spring, whereas the opposite situation was observed during post-bloom situations in late spring/early summer.